Governors and the Progressive movement - Berman, David R. (University Press Of Colorado, 2019)
"Comprehensive overview of the Progressive movement's unfolding at state level, and in existence at the time, as evidenced in the eyes and actions of governors. Exploring the personalities, ideas, and activities of well-known governors as well as lesser-known ones who deserve far more attention"--Provided by publisher